Clinical periodontal conditions in individuals after bariatric surgery: a systematic review and meta-analysis - Miranda dos Santos, Melanie Calheiros (2019)
The aim of the present study was to perform a systematic review and meta-analysis to assess the influence of bariatric surgery on the clinical periodontal conditions in patients with obesity. This review was based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses and registered at the International Prospective Registry of Systematic Reviews (CRD42018099313). A search was conducted by 2 investigators in the PubMed/MEDLINE, Web of Science, and Cochrane Library databases for relevant articles published up to May 2018. The inclusion criteria were randomized controlled trials, prospective and retrospective studies, observational studies, longitudinal studies, and cohort studies with at least 3 months of follow-up. No language restrictions were imposed. The exclusion criteria were studies that did not evaluate or report the periodontal measurements, cross-sectional studies (without follow-up after surgery), studies that performed periodontal treatment, and those with insufficient periodontal data. The meta-analysis was based on the Mantel-Haenszel method and inverse variance. The quantitative analysis revealed no statistically significant differences with regard to bleeding on probing (P = .9; mean deviation: -.70; confidence interval = -11.43 to 10.04) or probing pocket depth (P = .41; mean deviation: -.46; confidence interval = -1.55 to .63) before and after intervention. Clinical attachment loss showed a statistically significant difference (P = .0002; mean deviation: .18; confidence interval = .07-.30). It can be concluded that bariatric surgery does not influence bleeding on probing or probing pocket depth, but leads to a worsening of clinical attachment loss. (C) 2019 American Society for Bariatric Surgery. Published by Elsevier Inc. All rights reserved.